Pengaruh iklim organisasi dan kepuasan kerja serta komitmen organisasional terhadap kinerja karyawan - Arru Gideon Lineker; Tetra Hidayati; Siti Maria (INOVASI, 2016)
The purpose of this study is to Know and analyze the influence of organizational climate on employee performance of PT Adi Dharma in Balikpapan. Know and analyze the effect of job satisfaction on the performance of employees of PT Adi Dharma in Balikpapan. Know and analyze the influence of organizational commitment to employee performance PT Adi Dharma in Balikpapan. This research is an empirical study by all employees used as the sample of 55 employees. Data was analyzed using multiple regression with SPSS version 23.0. The results in this study showed that partially by using the t test showed that proven organizational climate variables significantly affect performance variables, variable job satisfaction proved no significant effect on the performance variables, variables of organizational commitment shown to significantly affect performance variables.Keyword: Organizational Climate and Job Satisfaction and Organizational Commitment on Employee Performance.